The plant gods? - Dewalt, Kevin; King, Rob (Canada : Filmwest Associates, 1993)
This documentary examines some of the key issues surrounding the fascinating and complex world of biotechnology, from the high-tech labs to the growing trends of North America
Editor, Ken Knawczyk ; photograph, Ian K. Rogers
Keywords: Biotechnology -- Research; Genetic engineering